Factors affecting transportation's development and spillover effects on neighboring provinces: the case of Ho Chi Minh, Vietnam - Vu Thi Kim Hanh; Nguyen Hong Nga (Cogent Business & Management, 2024)
The objective of this study is to explore the influence of various factors on transportation development, considering their spillover effects on Gross Domestic Product (GDP) growth in neighboring provinces. The study utilizes time-series data from the transportation industry in Ho Chi Minh, Vietnam. Accordingly, a theoretical framework is constructed based on foundational theories. The methodology involves Structural Equation Modeling (SEM) analysis and its five steps of Goodness of Fit testing. The key findings include: (1) Mobile phones positively influence, while corruption control and state investment negatively impact goods labor productivity; (2) Provincial Competitiveness Index (PCI) and state investment positively influence both people labor productivity and people capital productivity; (3) Regarding spillover effects on neighboring provinces, mobile phones have a negative influence, while PCI positively impacts the GDP growth of Binh Phuoc. Mobile phones negatively affect GDP growth in Vung Tau and Dong Nai, whereas corruption control positively affects it in these provinces. Therefore, with regard to institutions, the government should regulate transportation industry activities towards environmental friendliness, such as developing PCI in the direction of a green environment or investing in green fuel for the transportation industry. As corruption control has both positive and negative effects, we recommend increasing corruption control towards a sustainable economy. Regarding technology, since mobile phones have both positive and negative effects, we suggest finding a balance to boost goods labor productivity. These results offer transportation policymakers and managers both theoretical and practical perspectives to improve the transportation industry's development.Our study is an empirical investigation into the factors influencing the development of transportation and the spillover effects on neighboring provinces, with a focus on the case of Ho Chi Minh, Vietnam. Ho Chi Minh stands as the largest city and economic hub of Vietnam, playing a crucial role in the southern key economic region. The transportation industry's average contribution to Gross Regional Domestic Product (GRDP) in Ho Chi Minh was approximately 16% during the period from 2010 to 2020. However, a significant challenge emerges. From 2010 to 2020, just over 40% of enterprises in the transportation industry were profitable, with around 50% experiencing sales losses. Moreover, about 8% of enterprises encountered operational interruptions, temporary closures, or faced issues leading to dissolution or bankruptcy.
Keywords: 650; Transportation development; transportation physical factor; institutional factor; technological factor; SEM